Posterior rat eye during acute intraocular pressure elevation studied using polarization sensitive optical coherence tomography - Fialová, Stanislava (2019)
Polarization sensitive optical coherence tomography (PS-OCT) operating at 840 nm with axial resolution of 3.8 µm in tissue was used for investigating the posterior rat eye during an acute intraocular pressure (IOP) increase experiment. IOP was elevated in the eyes of anesthetized Sprague Dawley rats by cannulation of the anterior chamber. Three dimensional PS-OCT data sets were acquired at IOP levels between 14 mmHg and 105 mmHg. Maps of scleral birefringence, retinal nerve fiber layer (RNFL) retardation and relative RNFL/retina reflectivity were generated in the peripapillary area and quantitatively analyzed. All investigated parameters showed a substantial correlation with IOP. In the low IOP range of 14-45 mmHg only scleral birefringence showed statistically significant correlation. The polarization changes observed in the PS-OCT imaging study presented in this work suggest that birefringence of the sclera may be a promising IOP-related parameter to investigate.